CELL MANUFACTURING SEBAGAI STRATEGI PERUSAHAAN DALAM MENGHADAPI PERMINTAAN YANG FLUKTUATIF - Irwan, Herry (Universitas Riau Kepulauan, 2013)
Short cycle time, demand is unpredictable and types of products in an industry have forced a manufacturing company in operation for more efficient and efektive in meeting the changing demands. Traditional manufacturing systems as well as job shop and flow line can not handle the situation. Cell manufacturing jobshop that combines flexibility and production speed in a flow line is an alternative process flow that is able to solve the above problems. Through the optimization of the operator is one way companies stay competitive with lower production costs in this case is the operational cost of the wages of employees directly.